The relationship between e-Health literacy and cyberchondria in Iranian students of health sciences - Kalantari, Amirreza; Valizadeh-Haghi, Saeideh; Starcevic, Vladan; Shahbodaghi, Azam; Rahmatizadeh, Shahabedin; Zayeri, Farid; Khazaal, Yasser (Frontiers in Psychiatry, 2025)
IntroductionCyberchondria has been growing in recent years. Understanding the relationship between e-Health Literacy and Cyberchondria is important, as enhancing e-Health Literacy perhaps empower individuals to navigate online health information without experiencing Cyberchondria. The present study aimed to investigate levels of e-Health Literacy and Cyberchondria in Iranian students of health sciences and examine the relationship between e-Health Literacy and Cyberchondria.MethodsTo assess this, a sample of 241 undergraduate students of health sciences were recruited. They were administered two instruments for the assessment of e-Health Literacy and Cyberchondria: eHealth Literacy Scale (eHEALS) and Cyberchondria Severity Scale (CSS).ResultsFindings showed that the mean total CSS score was 72.61, while the mean total eHEALS score was 28.50. Students who reported having a chronic disease had a significantly higher mean total CSS score than those who considered themselves healthy. The correlation between the total eHEALS scores and total CSS scores was very weak (r = -0.074). Total eHEALS scores correlated significantly and negatively with the distress (r = -0.288) and compulsion (r = -0.163) CSS subscales and significantly and positively with the reassurance (r = 0.174) and excessiveness (r = 0.141) CSS subscales.ConclusionThe relationship between e-health literacy and cyberchondria is complex. While people may develop cyberchondria irrespective of the level of their e-health literacy, a high level of e-health literacy may be protective in terms of alleviating distress and problems in functioning that occur with excessive online health searches. These findings are likely to inform future studies in this area.